Hidden pull rod glass daylighting roof - XU LI; SHI SHENGXIANG; QI HAIYAN; JIANG YINGYING; SHEN ZHIYU; WU LIANGJUN; ZHU CHENGHAO; FAN KAOPING; ZHU QINBIAO; LU YUQI; CHEN JIANWEI; LIU DAKUI; et al. (2023)
The utility model belongs to the technical field of building daylighting roofs, and particularly relates to a hidden pull rod glass daylighting roof which comprises a glass panel, a vertical supporting structure, a transverse supporting structure and a deflection control structure. Meanwhile, the two adjacent glass panels are connected in the second direction through the hidden transverse supporting structures, the dynamic effects of the daylighting roof in the aspects of hue, transparency, brightness and the like are guaranteed from the building appearance effect of the daylighting roof, and the whole building is more attractive and uniform; and meanwhile, the joints and gaps between the structures are filled with sealants or ethylene-propylene-diene monomer rubber strips, so that a plurality of waterproof layers are formed, the good waterproof effect is achieved, and the leakage risk is reduced. 本实用新型属于建筑物采光顶技术领域，具体涉及一种隐藏式拉杆玻璃采光顶，包括：玻璃面板、竖向支撑结构、横向支撑结构和挠度控制结构，通过设置竖向支撑结构在第一方向上支撑玻璃面板，同时通过隐藏式的横向支撑结构在第二方向上连接相邻两个